Marine organisms as a source of natural matrix for bone tissue engineering. Issue 2 (1st February 2019) - Lalzawmliana, V.; Anand, Akrity; Mukherjee, Prasenjit; Chaudhuri, Shubhamitra; Kundu, Biswanath; Nandi, Samit Kumar; Thakur, Narsinh L.
Abstract: It is a huge challenge to develop an effective regenerative approach which can be employed to restore diseased or defective part of the bone to its original anatomical and physiological function. Exploration of rich biodiversity in marine ecosystem is one of the most exciting prospects for development of biomaterial for bone tissue engineering. Due to their organic nature, the materials which are fabricated from natural environment are usually safe, biocompatible, biodegradable and osteoconductive which stimulates osteogenesis. Furthermore, marine derived biomaterials are superior to the current available materials which are employed for either in vitro or in vivo grafts or scaffolds as there are some limitations with the present strategies. Regardless of their immense potential, the natural marine resources are enormously unexploited. This review recounts various biomaterials which can be extracted from marine organism for future medical application.